2021
DOI: 10.1093/eurheartj/ehab153
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram screening for aortic valve stenosis using artificial intelligence

Abstract: Aims Early detection of aortic stenosis (AS) is becoming increasingly important with a better outcome after aortic valve replacement in asymptomatic severe AS patients and a poor outcome in moderate AS. We aimed to develop artificial intelligence-enabled electrocardiogram (AI-ECG) using a convolutional neural network to identify patients with moderate to severe AS. Methods and results Between 1989 and 2019, 258 607 adults [me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
103
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 31 publications
2
103
0
2
Order By: Relevance
“…However and as stated by the authors, conclusions of this visualization have to be drawn carefully, as it has been shown that class activation mapping can fail to properly localize objects in an image if the image contains multiple occurrences of the same classification (as it is the case in a 12-lead ECG) [ 13 ]. Last, Cohen-Shelly et al showed the feasibility of artificial intelligence based screening for aortic valve stenosis using standard 12-lead ECG [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However and as stated by the authors, conclusions of this visualization have to be drawn carefully, as it has been shown that class activation mapping can fail to properly localize objects in an image if the image contains multiple occurrences of the same classification (as it is the case in a 12-lead ECG) [ 13 ]. Last, Cohen-Shelly et al showed the feasibility of artificial intelligence based screening for aortic valve stenosis using standard 12-lead ECG [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…objects in an image if the image contains multiple occurrences of the same classification (as it is the case in a 12-lead ECG) [13]. Last, Cohen-Shelly et al showed the feasibility of artificial intelligence based screening for aortic valve stenosis using standard 12-lead ECG [39].…”
Section: Plos Onementioning
confidence: 99%
“…showed that the TP interval and U waves in the right precordial leads were weighted the most heavily for determining the presence of AS. 2 Typical ECG findings for left ventricular hypertrophy were not weighted in the developed AI. Although those findings and the methodology involved will inspire many researchers, further research is needed to understand the exact meaning of the former.…”
mentioning
confidence: 98%
“…developed and validated a DL model for detecting aortic stenosis (AS) using electrocardiography (ECG), and their results are published in this issue of the European Heart Journal . 2 The authors have shown that AI using ECG can identify patients with moderate or severe AS, and might be able to predict developing AS by comparing false-positive and true-negative groups in subgroup analysis. Through learning an implicit representation, the DL model is effective in discovering diverse features based on subtle changes in ECG and creating an algorithm from complex and non-linear ECG data.…”
mentioning
confidence: 99%
See 1 more Smart Citation